2011
DOI: 10.1016/j.toxicon.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acids critical for the cytotoxicity of Shiga toxin 1 and 2 in Saccharomyces Cerevisiae

Abstract: Shiga toxins (Stx1 and Stx2) are produced by E. coli O157:H7, which is a leading cause of foodborne illness. The A subunits of Stx1 (Stx1A) and Stx2 (Stx2A) are ribosome inactivating proteins (RIPs) that inhibit translation by removing an adenine from the highly conserved α-sarcin ricin loop (SRL) of the large rRNA. Here, we used mutagenesis in S. cerevisiae to identify residues critical for cytotoxicity of Stx1A and Stx2A. The A subunits depurinated the SRL, inhibited translation and caused apoptotic-like cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…To compare the cytotoxicities of the A1 subunits of Stx1 and Stx2 in vivo, the mature A1 subunits were expressed in the yeast S. cerevisiae, with the V5 and 10ϫHis epitope tags under the tightly controlled GAL1 promoter. Previously reported results indicated that the V5 and 10ϫHis epitope tags do not affect the activity of the A subunits (39,40). Irreversible growth inhibition by Stx1A1 and Stx2A1 was determined by plating cells onto medium containing 2% dextrose after galactose induction for the indicated times in liquid medium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To compare the cytotoxicities of the A1 subunits of Stx1 and Stx2 in vivo, the mature A1 subunits were expressed in the yeast S. cerevisiae, with the V5 and 10ϫHis epitope tags under the tightly controlled GAL1 promoter. Previously reported results indicated that the V5 and 10ϫHis epitope tags do not affect the activity of the A subunits (39,40). Irreversible growth inhibition by Stx1A1 and Stx2A1 was determined by plating cells onto medium containing 2% dextrose after galactose induction for the indicated times in liquid medium.…”
Section: Resultsmentioning
confidence: 99%
“…Its interaction with the negatively charged RNA may reduce the availability of the active-site residues to perform catalysis. Previously reported results showed that mutations of residues at the active sites of Stx1A and Stx2A affect cytotoxicity and catalytic activity differently (39). The residues previously shown to be involved in the depurination reaction in Stx1 and Stx2 (E167 and R170) are more exposed in Stx2A1 than in Stx1A1 (39).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Early studies using the holotoxins identified Glu167 and Arg170 of the A1 subunits as important for catalytic activity (33)(34)(35)(36). The corresponding Arg180 in RTA is proposed to promote cleavage of the adenine by protonating position N3 of the adenine (37)(38)(39), while the corresponding Glu177 polarizes a surrounding water molecule to produce a hydroxide ion that aids in the cleavage of adenine.…”
Section: Discussionmentioning
confidence: 99%